2022
DOI: 10.1111/evj.13598
|View full text |Cite
|
Sign up to set email alerts
|

Training the equine respiratory muscles: Ultrasonographic measurement of muscle size

Abstract: Background: Limited information exists regarding changes in the size of respiratory and locomotor muscles in response to exercise training in the Thoroughbred racehorse. Objectives: To describe and compare the responses of the respiratory and locomotor muscles to conventional exercise training and inspiratory muscle training (IMT). Study design: Prospective randomised controlled trial. Methods: Thoroughbred racehorses, in training for competition in National Hunt races, were recruited from two training establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The results presented here indicate that both conventional race training and high‐load IMT appear to increase the strength of the equine diaphragm, in line with results in human subjects 8,10 . A linked investigation also demonstrated an increase in diaphragm thickness, measured ultrasonographically, in association with training 1 . Although the results of the linked investigation did not show an increase in the size of the muscles of the upper airway with IMT, previous studies have indicated the potential use of IMT for the management of dynamic upper airway obstruction in both equine and human athletes 22,27 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The results presented here indicate that both conventional race training and high‐load IMT appear to increase the strength of the equine diaphragm, in line with results in human subjects 8,10 . A linked investigation also demonstrated an increase in diaphragm thickness, measured ultrasonographically, in association with training 1 . Although the results of the linked investigation did not show an increase in the size of the muscles of the upper airway with IMT, previous studies have indicated the potential use of IMT for the management of dynamic upper airway obstruction in both equine and human athletes 22,27 .…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the association between IMT, IMSi, and race performance were not assessed in this investigation as the number of horses included in the study, and the time between examinations, were both deemed too small to obtain a meaningful difference. This study was performed alongside a linked investigation conducted in a larger population of horses which did explore the association between ultrasound measurement of respiratory muscle size and performance ratings 1 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations